Effect of the Proportion of Kepok Banana Flour (Musa Acuminata × Balbisiana) and Lima Bean Flour (Phaseolus Lunatus L.) on the Chemical, Physical, and Organoleptic Characteristics Of Lidah Kucing Cookies - Novelina Novelina; Aisyah Aisyah; Cear Wellya Refdi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Indonesia's dependence on imported wheat flour has encouraged the development of food products based on local raw materials. This study aimed to evaluate the effect of the proportion of kepok banana flour (Musa acuminata × balbisiana) and lima bean flour (Phaseolus lunatus L.) on the chemical, physical, and organoleptic characteristics of lidah kucing cookies and to determine the best formulation. The study employed a Completely Randomized Design (CRD) consisting of five treatments with three replications. Treatments were based on different proportions of wheat flour, kepok banana flour, and lima bean flour. Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan's New Multiple Range Test (DNMRT) at a 5% significance level. The results showed that flour proportion significantly affected (p < 0.05) moisture content, ash content, protein content, fat content, carbohydrate content, crude fiber content, hardness, and color of lidah kucing cookies. However, it did not significantly affect panelists' preference levels for aroma, taste, and texture. The best formulation was treatment E, consisting of 50% wheat flour, 20% kepok banana flour, and 30% lima bean flour, which produced cookies with 3.62% moisture content, 2.05% ash content, 9.49% protein, 22.95% fat, 61.88% carbohydrates, 2.10% crude fiber, and a hardness value of 137.20 N/cm². The panelists’ preference scores for color, aroma, taste, and texture were 3.84, 3.88, 4.16, and 4.20, respectively. These findings indicate that the use of kepok banana flour and lima bean flour as partial substitutes for wheat flour can enhance the protein and fiber content of lidah kucing cookies while maintaining consumer acceptability Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation, and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action